Chronic Exposure to Cigarette Smoke Affects the Ileum and Colon of Guinea Pigs Differently. Relaxin (RLX-2, Serelaxin) Prevents Most Local Damage - Traini, Chiara; Nistri, Silvia; Calosi, Laura; Vannucchi, Maria Giuliana (Frontiers in Pharmacology, 2022)
Cigarette smoking (CS) cause of several organ and apparatus diseases. The effects of smoke in the gut are partially known. Accumulating evidence has shown a relationship between smoke and inflammatory bowel disease, prompting to investigate the mechanisms of action of smoking in animal models. Despite the role played by the neuropeptides in gut inflammation, there are not reports on their role in animal models of smoking exposure. The hormone relaxin has shown anti-inflammatory properties in the intestine and it might represent a putative therapy to prevent gut damages caused by smoke. Presently, we investigated the effects of chronic smoke exposure on inflammation, mucosal secretion, vasoactive intestinal peptide (VIP), and substance P (SP) expression in the ileum and colon of guinea pigs. We also verify the ability of relaxin to counter smoke-induced effects. Smoke impacted plasma CO. In the ileum, it induced inflammatory infiltrates, fibrosis and acidic mucin production, reduced blood vessel area, decreased c-kit+ mast cells and VIP+ neurons, increased the SP+ nerve fibers. In the colon, it reduced the blood vessel area and the goblet cell area, decreased c-kit+ mast cells, VIP+ neurons and SP+ nerve fibers. Relaxin prevented most of the smoking-induced changes in the ileum while it was less effective in the colon. This study shows the diverse sensitivity to CS between ileum and colon and demonstrates that both VIP and SP are affected by smoking. Relaxin efficacy propose the hormone as a potential anti-inflammatory therapeutic to counteract gut damages in humans affected by inflammatory bowel diseases.